Inducible Costimulator Contributes to Methicillin-Resistant Staphylococcus aureus Pneumonia - Pires, Silvia (J Infect Dis, 2018)
Staphylococcus aureus is a major cause of both community- and healthcare-acquired pneumonias. Inducible costimulator (ICOS) is part of the CD28 family of proteins and is a target for immune checkpoint therapy. We found ICOS highly expressed on activated CD4 cells in response to S. aureus. In the absence of ICOS, mice had improved survival in a pneumonia model with the methicillin-resistant Staphylococcus aureus (MRSA) strain USA300 and significant reductions in bacterial burden in a nonlethal acute pneumonia model. Infected Icos(-/-) mice had major reductions in several proinflammatory cytokines, neutrophils, inflammatory monocytes, and eosinophils compared to infected wild-type mice, while there was improved expression of CD11c and macrophage receptor with collagenous structure on the surface of alveolar macrophages. Early during infection infected Icos(-/-) mice had increased numbers of alveolar macrophages and expression of several surface markers on alveolar macrophages and neutrophils. ICOS signaling also contributed to the pathogenesis of the airway pathogens Klebsiella pneumoniae, Pseudomonas aeruginosa, and Streptococcus pneumoniae, and neutralizing antibody to ICOS led to improved clearance of S. aureus from the airway. Our results indicate that ICOS plays a significant role in orchestrating the innate immune response to S. aureus and other airway pathogens, and could be a potential immunomodulatory target to attenuate S. aureus–related immunopathology.